Retrospective Study of Anesthesias in Dogs and Cats Underwent to Neurosurgery - Zang, Luciana; Araújo, Ana Cristina Pacheco de; Ferreira, Márcio Poletto (Acta Scientiae Veterinariae, 2016)
Background: The goal of anesthesia in patients with neurological diseases is to maintain the homeostasis of the central nervous system, focusing on intracranial pressure and pain during the intraoperative period. The purpose of this study was to evaluate the anesthesia performed between January 2010 and January 2016 at the Veterinary Clinical Hospital at the Federal University of Rio Grande do Sul and correlate the types of surgeries, drugs used in the pre-anesthetic medication, induction, pain control, and the development of complications during the procedure. Materials, Methods & Results: The medical records of 242 patients, who presented with neurological signs of spinal cord compression or traumatic brain injury, were assessed. Only 70 patients who underwent surgery had properly documented and detailed anesthesia records. Of these 70, there were 32 male and 38 female animals, with one feline and 69 canines. Their weights on the day of surgery ranged between 1.5 kg and 38 kg and their ages ranged from six months up to 13 years. We evaluated 74 surgeries because four patients underwent two separate surgeries. There were 38 hemilaminectomies, 14 ventral slots, seven vertebral stabilizations (one atlantoaxial instability and six vertebral fractures), six dorsal laminectomies, four pediculectomies, two fenestrations with hemilaminectomy, one durotomy with hemilaminectomy, one minihemilaminectomy, and one tumor removal. The complications observed were bradycardia (25/74), systemic hypotension (49/74), systemic hypertension, (21/74) and death (4/74). There was a great variation in the pre-anesthetic medication; either combinations of two or more drugs, one drug, or no medication was used. The most common drug used for induction of the patient was propofol, which was used in 46 cases as single agent and in 26 cases in combination with other drugs. In 43 patients, the majority of nociception control during the intraoperative period was achieved with continuous infusions of fentanyl combined with lidocaine, while some used ketamine. Pain control for the remaining 15 patients was accomplished with drug boluses. In two cases, the choice of opioid in the pre-anesthetic medication was repeated. Fourteen patients had remained without analgesia during surgery. No correlation was observed between the frequency of complications and the type of surgery performed, the medications used for induction of the patient, or the method of control of nociceptive stimuli during surgery. Continuous infusions were used frequently for pain control during surgery, however no significant correlation with complications was observed. Discussion: The high prevalence of neurological diseases that affect the spinal cord makes spinal surgery one of the most frequent neurosurgeries. The risk of complications in spinal surgery is affected by hemodynamics of the patient and may lead to death during the procedure. The most frequent complications are bradycardia, hypotension, cardiac electrophysiological changes, apnea, hemorrhage, and death. The survey identified bradycardia, hypotension, hypertension, and death as the major complications. The most frequent method of intraoperative analgesia was a continuous infusion, due to its benefits when compared to other methods of analgesia. When compared to previous studies, the present study showed similar complications that had no correlation wtih the type of surgery or anesthesia protocol.